Evidence of widespread cerebral microglial activation in amyotrophic lateral sclerosis: an [11C](R)-PK11195 positron emission tomography study. - Turner, M; Cagnin, A; Turkheimer, F; Miller, C; Shaw, C; Brooks, D; Leigh, P; Banati, R (2004)
Microglial activation is implicated in the pathogenesis of ALS and can be detected in animal models of the disease that demonstrate increased survival when treated with anti-inflammatory drugs. PK11195 is a ligand for the "peripheral benzodiazepine binding site" expressed by activated microglia. Ten ALS patients and 14 healthy controls underwent [(11)C](R)-PK11195 PET of the brain. Volumes of interest were defined to obtain [(11)C](R)-PK11195 regional binding potential values for motor and "extra-motor" regions. Significantly increased binding was found in motor cortex (P = 0.003), pons (P = 0.004), dorsolateral prefrontal cortex (P = 0.010) and thalamus (P = 0.005) in the ALS patients, with significant correlation between binding in the motor cortex and the burden of upper motor neuron signs clinically (r = 0.73, P = 0.009). These findings indicate that cerebral microglial activation can be detected in vivo during the evolution of ALS, and support the previous observations that cerebral pathology is widespread. They also argue for the development of therapeutic strategies aimed at inflammatory pathways.